Analisis Berkas Rekam Medis Rawat Inap Pada Kasus Operasi Di Rumah Sakit Pusat Pertamina Jakarta Selatan - Nungki Annisa Pratiwi; Demiawan Rachmatta Putro Mudiono; Djasmanto Djasmanto (Indonesian Journal Publisher, 2022)
Based on the results of observations made at Pertamina Central Hospital, it was found that several inpatient medical record file forms, especially in cases of surgery, were related to filling out forms that were not 100% complete and there was no evaluation of the completeness of inpatient medical record files in surgical cases. The purpose of this study was to analyze the completeness of inpatient medical record files, especially cases of surgery at Pertamina Central Hospital in February 2022. This research method used qualitative descriptive. Sampling using the Slovin formula with a population of 200 and the sample results obtained 67 samples. The results of this study obtained that the completeness of filling out the medical record file operation form in the complete category was 43 medical record files (64%) and 24 medical record files were incomplete (36%). The conclusion of this study is that the completeness of inpatient medical record files in surgical cases, especially related to filling out forms at Pertamina Central Hospital is categorized as incomplete because filling out forms is not 100% complete.